2014
DOI: 10.1080/00325481.2015.998158
|View full text |Cite
|
Sign up to set email alerts
|

Reversible morbidity markers in subclinical hypothyroidism

Abstract: Future large, well-controlled studies will not only clarify the role of SCH but also help identify patients for whom levothyroxine treatment will provide the most benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…We also observed no relationship between SCH and depression in older patients. A probable interpretation of this disparity could be the over-diagnosis of SCH among the elderly due to the lack of age-associated serum TSH reference ranges in the original studies included in the meta-analysis 32 . Indeed, movement of the serum TSH distribution curve to higher levels during ordinary ageing may result in misclassification of older patients as suffering from SCH 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…We also observed no relationship between SCH and depression in older patients. A probable interpretation of this disparity could be the over-diagnosis of SCH among the elderly due to the lack of age-associated serum TSH reference ranges in the original studies included in the meta-analysis 32 . Indeed, movement of the serum TSH distribution curve to higher levels during ordinary ageing may result in misclassification of older patients as suffering from SCH 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Because SCH has an obviously adverse impact on cardiovascular function, it has been proposed that restoring TSH level to the normal range through LT4 therapy may reverse its negative impact on cardiovascular function ( 5 , 9 , 66 ). Some studies have shown that certain risk factors of cardiovascular disease can be reversed by LT4 therapy among SCH patients ( 65 , 67 ). Though a meta-analysis published in 2007 concluded that LT4 therapy was not effective in decreasing cardiovascular morbidity in SCH patients ( 68 ), several recent studies found that LT4 therapy could reverse some detrimental impacts caused by SCH ( 21 , 22 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The American Thyroid Association recommends that patients with hypothyroidism and thyroid peroxidase antibodies in pregnancy should be treated with levothyroxine sodium tablets. The American Endocrine Society and the European Thyroid Association recommend levothyroxine sodium tablets for SCH women during pregnancy (14). Moreover, whether levothyroxine sodium tablets can improve the harm caused by SCH to pregnant women and their offspring has not yet formed a clear conclusion (15).…”
Section: Introductionmentioning
confidence: 99%